Perspectives on Motivation and Change in an Intervention for Men Who Use Substances and Perpetrate Intimate Partner Abuse: Findings From a Qualitative Evaluation of the Advance Intervention - Dheensa, Sandi (Journal of interpersonal violence, 2022)
Despite consistent evidence that substance use is a contributory risk factor for perpetration of intimate partner abuse (IPA), little evidence exists for effective interventions for male IPA perpetrators who use substances. The Advance intervention aimed to meet this need. This 16-week intervention addressed both IPA and substance use, and was for men accessing substance use treatment who had perpetrated IPA toward a female (ex-)partner within the last 12?months. Two key theories underpinned the intervention: goal theory and self-regulation theory. In this article, we aim to illustrate the views of men and substance use treatment staff on men?s motivations to change, the ways in which men and staff said that men had changed their behavior, and the aspects of the intervention that they reported were key in the process of change. Using framework analysis, we analyzed data from 12 men who took part in the intervention as well as 31 staff members from substance use treatment services. Our five overarching themes were personal goal setting and motivation; recognition of IPA and the substance using lifestyle; improved self-regulation; considering the impact on others; and learning together in a group. Men and staff valued having a program that integrated IPA and substance use and thought the program was unique and much needed. Moreover, our findings suggest that goal theory, self-regulation, and more broadly, motivational and strengths-based approaches with practice-based activities, may be beneficial for effecting change in the substance using perpetrator population. However, further research is needed to determine the effectiveness of the intervention. Overall, our findings highlight the value of using qualitative outcome measures of perpetrator programs to complement quantitative measures of impact.